Pengaruh Ukuran Perusahaan,Profitabilitas,Pertumbuhan Perusahaan Dan Laverage Terhadap Nilai Perusahaan Pada Sektor Properti Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia - Annisa Nauli Sinaga; Perdy Perdy; Agustina Teresia Purba (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to examine and analyze how the influence of company size, profitability, company growth and leverage on firm value in the property and real estate sectors listed on the Indonesia Stock Exchange in 2017-2019, either partially or simultaneously. This research is a quantitative research. The population in this study is the property and real estate sector companies totaling 58 companies. The sample of this research is 27 companies selected by purposive sampling technique. The statistical method used is multiple linear regression analysis. The results of the study indicate that company size, company growth and leverage have no effect on company value. While profitability has a significant effect on firm value. And simultaneously Company Size, Profitability, Company Growth and Leverage have an effect on Company Value. The magnitude of the coefficient of determination is 33.1% while the remaining 66.9% Firm Value is explained by other variables not examined in this study. The conclusion of this study is that only profitability has a significant effect on firm value in the property and real estate sectors listed on the Indonesia Stock Exchange in 2017-2019. Keywords : Company Size, Profitability, Company Growth, Leverage, Firm Value